Epidemiology, prevalence, and associated factors of oral candidiasis in HIV patients from southwest Iran in post-highly active antiretroviral therapy era - Erfaninejad, Maryam; Zarei Mahmoudabadi, Ali; Maraghi, Elham; Hashemzadeh, Mohammad; Fatahinia, Mahnaz (Frontiers in Microbiology, 2022)
Background Oral candidiasis (OC) is one of the most common opportunistic fungal infections among people living with HIV/AIDS (PLWHA). The prevalence of OC and Candida profiles among HIV-infected patients might be changing in the era of Highly Active Antiretroviral Therapy (HAART). This study aimed to identify Candida spp., determine OC prevalence and associated risk factors for PLWHA. Methods OC prevalence was explored in oral swabs of 276 patients who referred for consultation at Behavioral Diseases Counseling Center (BDCC). Clinical symptoms, culture and molecular assays were used for OC detection. In statistical analysis, we assessed socio-demographic characteristics, clinical information and treatment history of some infections. Results The overall prevalence of OC was 41%. Candida albicans (64.6%) was the most common species, followed by C. glabrata (26.5%) and C. dubliniensis (19.5%). C. famata, C. africana, C. stellatoidea as the first fungi isolated from OC in PLWHA from southwest Iran. In 36.3% of patients, mixed cultures of more than one species were observed. Body mass index (BMI) [OR, 0.947; CI, 0.89-0.99; p=0.045] and CD4 count ≤200 cells/mm3 [OR, 4.365; CI, 1.73-10.98; p=0.002] were the predictors of OC in the final model of multiple logistic regression analysis. Education level, addiction status, sexual behaviors, chest X-ray, other infections and WHO clinical stage were other important risk factors for OC. Conclusions OC remains a significant opportunistic infection in post-HAART era among PLWHA. Despite the increasing prevalence of NAC species, C. albicans (64.6%) was still the predominant species. Our results showed that low BMI with OC indicates treatment failure (i.e. failure to increase CD4 count or suppress viral load). Also, low CD4 counts (≤200 cells/mm3) in HIV patients show an impaired immune status, and our findings emphasize that OC can be a clinical indicator of HIV infection in individuals who do not know their HIV status or have failed treatment.